2017
DOI: 10.1093/icvts/ivw426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender on long-term outcomes after surgical repair for acute Stanford A aortic dissection: a propensity score matched analysis†

Abstract: Considering patients with similar risk profiles, female gender per se is not associated with worse long-term survival and freedom from stroke after surgical aortic repair. Moreover, female patients might even benefit from a smoother early postoperative course and lower incidence of early postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 13 publications
3
31
0
Order By: Relevance
“…Several studies indicated a poor outcome after surgery for AADA in women [5,11] and Nienaber et al [5] found a higher in-hospital mortality in women (32% vs. 22%), more in-hospital complications and a worse surgical outcome despite similar time from symptom onset to diagnosis, surgical technique and hemodynamics. In contrast female gender was not associated with worse early and long-term outcomes in several recent studies [3,4,12], which was confirmed by our results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Several studies indicated a poor outcome after surgery for AADA in women [5,11] and Nienaber et al [5] found a higher in-hospital mortality in women (32% vs. 22%), more in-hospital complications and a worse surgical outcome despite similar time from symptom onset to diagnosis, surgical technique and hemodynamics. In contrast female gender was not associated with worse early and long-term outcomes in several recent studies [3,4,12], which was confirmed by our results.…”
Section: Discussionsupporting
confidence: 92%
“…Men presented with a higher creatinine level and tended to have a higher rate of chronic renal insufficiency, however, this difference was not significant. Consistent with our findings Fukui et al [4], Conway et al [3] and Sabashnikov et al [12] reported increased creatinine levels in men despite no substantial disparities in GFR and rate of chronic renal failure, concluding that creatinine is of lower clinical relevance [12]. Moreover, creatinine levels are physiologically higher in men, as indicated by sex-specific standard values.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Sabashnikov et al described surgical procedure for Stanford A AAD. 8,9 Depending on the identification of the location of the aortic entry tear in the CT scan before surgery extent of surgery was planned. Moreover, if the exact location of the primary aortic entry tear was unclear, extent of aortic repair and the very entry tear site were in detail reevaluated during surgery due to proper intraoperative visual inspection to exclude a possible communication between lumina.…”
Section: Surgical Proceduresmentioning
confidence: 99%